An Enterprise Architecture in the Construction Management Software using the Business Model Canvas - Susatyo, R Wahyu Indra; Indrajit, Eko; Dazki, Erick (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Indonesia's construction industry has boomed over the past decade, acting as a powerful engine for the nation's economic growth. However, this success story comes with a growing list of challenges. Construction projects are becoming increasingly intricate, demanding not only efficiency and quality but also enhanced safety and a minimized environmental footprint. To tackle these complexities, the industry is undergoing a crucial transformation towards "smart construction." This approach leverages the power of information and communication technology (ICT) throughout the entire project lifecycle, from planning and design to execution and maintenance. By integrating ICT tools like Building Information Modeling (BIM) and cloud-based project management platforms, smart construction streamlines processes, minimizes errors, and optimizes resource allocation, ultimately leading to improved efficiency, enhanced worker safety, and a reduction in environmental impact. A key pillar of smart construction lies in the integration of enterprise architecture (EA) within construction management software. EA provides a structured framework for aligning IT systems with construction businesses' specific goals and objectives. This ensures that software development and management are adaptable to evolving industry needs and foster continuous innovation. This research delves into the application of EA within the construction management software industry, specifically focusing on the TOGAF Architecture Development Method (ADM). By exploring EA through this established framework, the research aims to shed light on how the construction industry in Indonesia can leverage technology to its fullest potential. This will ensure continued growth within the sector and contribute to a lasting positive impact on the nation's economy.